Interactions Between Odorants and Glutathione Transferases in the Human Olfactory Cleft. (21st August 2020) - Schwartz, Mathieu; Menetrier, Franck; Heydel, Jean-Marie; Chavanne, Evelyne; Faure, Philippe; Labrousse, Marc; Lirussi, Frédéric; Canon, Francis; Mannervik, Bengt; Briand, Loïc; Neiers, Fabrice
Abstract: Xenobiotic metabolizing enzymes and other proteins, including odorant-binding proteins located in the nasal epithelium and mucus, participate in a series of processes modulating the concentration of odorants in the environment of olfactory receptors (ORs) and finely impact odor perception. These enzymes and transporters are thought to participate in odorant degradation or transport. Odorant biotransformation results in 1) changes in the odorant quantity up to their clearance and the termination of signaling and 2) the formation of new odorant stimuli (metabolites). Enzymes, such as cytochrome P450 and glutathione transferases (GSTs), have been proposed to participate in odorant clearance in insects and mammals as odorant metabolizing enzymes. This study aims to explore the function of GSTs in human olfaction. Using immunohistochemical methods, GSTs were found to be localized in human tissues surrounding the olfactory epithelium. Then, the activity of 2 members of the GST family toward odorants was measured using heterologously expressed enzymes. The interactions/reactions with odorants were further characterized using a combination of enzymatic techniques. Furthermore, the structure of the complex between human GSTA1 and the glutathione conjugate of an odorant was determined by X-ray crystallography. Our results strongly suggest the role of human GSTs in the modulation of odorant availability to ORs in the peripheral olfactory process.